A feature-based analysis identifies COL1A2 as a regulator in pancreatic cancer. (1st January 2019) - Wu, Jie; Liu, Jing; Wei, XiaoQing; Yu, Qi; Niu, XiangHuan; Tang, ShuHong; Song, Lei
Abstract: This study aimed to identify genetic biomarkers in pancreatic cancer (PC) and explore its function in PC via a feature-base analysis of bioinformatics. OMIM and DisGeNET databases discovered 209 PC connected genes and then 516 connected genes were identified. We selected 29 genes according to optimal features and chose COL1A2, which had the highest expression, for the following experiment. The expression of COL1A2 was determined by qRT-PCR; cell proliferation was determined by MTT assay; migration and invasion after COL1A2 and miR-25-3p transfection was evaluated by Transwell assay. COL1A2 presented the highest expression in PC tissues, which was validated in functional experiments. MiR-25-3p suppressed the expression of COL1A2 in cell lines and inhibited migration, invasion and proliferation of PC cells. MiR-25-3p could suppress the expression of COL1A2 and inhibit the proliferation, migration and invasion of PC cells which provided a new idea for the detection and treatment of PC.